Pengaruh Good Corporate Governance Terhadap Pemilihan Auditor (Studi Empiris Pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024) - M. Bassu Airlangga; Tertiarto Wahyudi; Emylia Yuniarti; Nilam Kesuma (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines the importance of auditing in ensuring transparency and credibility of financial statements and highlights inconsistencies in prior findings regarding the influence of Good Corporate Governance (GCG) on auditor selection. The objective is to analyze the effect of board structure, institutional ownership, ownership structure, firm risk, and firm size on auditor choice in manufacturing companies listed on the Indonesia Stock Exchange during 2022–2024. This research employs a quantitative approach with a causal design using panel data derived from secondary sources. Data were analyzed using logistic regression to test the effect of independent variables on auditor selection as a dummy variable. The results show that board structure, institutional ownership, and firm size have a positive and significant effect on auditor selection. Conversely, ownership structure has no significant effect, while firm risk shows a significant negative effect on the likelihood of choosing Big Four auditors. The model demonstrates good predictive ability and explains 42% of the variation in auditor selection decisions. In conclusion, not all GCG mechanisms consistently influence auditor selection, as internal company characteristics remain key determinants in audit decisions.